Cryptotanshinone Attenuates Inflammatory Response of Microglial Cells via the Nrf2/HO-1 Pathway - Zhou, Yang; Wang, Xiao; Ying, Weihai; Wu, Danhong; Zhong, Ping (Frontiers in Neuroscience, 2019)
Cryptotanshinone (CTN), a monomer compound extracted from the dried roots and rhizomes of Salvia miltiorrhiza Bge, has a variety of pharmacological effects. However, little research has been done on the mechanism of CTN in attenuating neuroinflammation. The present study aimed to investigate whether CTN can ameliorate neuroinflammation induced by lipopolysaccharide (LPS) through the Nrf2/HO-1 signal pathway in BV-2 microglial cells. We found that CTN attenuated the upregulated expression of iNOS, COX2, NLRP3, and NO induced by LPS in microglial cells. In addition, it curtailed the increased release of pro-inflammatory cytokines such as IL-1β, IL-6, and TNFα in LPS-activated microglial cells. Furthermore, CTN significantly increased the levels of NF-κB, Nrf2, HO-1, and Akt proteins. We demonstrated that the anti-inflammatory action of CTN in BV-2 microglial cells was partially due to the activation of the Nrf2/HO-1 pathway, which was regulated by the PI3K/Akt signaling pathway. Taken together, our results indicated that CTN downregulated the production and release of proinflammatory mediators in BV-2 microglial cells through activating the Nrf2/HO-1 pathway and subsequently protected neurons from inflammatory injury.